In vitro evaluation of marginal fit of zirconia-reinforced lithium silicate laminate veneers at two thicknesses using different CAD/CAM systems - El-Mahdy, Manar Ahmed; Aboelfadl, Ahmed Khaled; Wahsh, Marwa Mohamed (Brazilian Dental Science, 2020)
ABSTRACT Objective: The purpose of this in vitro study was to evaluate the marginal fit of laminate veneers made of zirconia-reinforced lithium silicate with two thicknesses using different CAD/CAM systems. Material and methods: 42 Laminate veneers milled from zirconia-reinforced lithium silicate were divided into three main groups according to milling machine used into: group X5, laminate veneers fabricated by inLab MCX5 milling machine; group CM, laminate veneers fabricated by Ceramill motion 2; and group XL, laminate veneers fabricated by inLab MCXL. Each group was divided into two subgroups according to veneer thickness into: subgroup I, 0.5 mm thickness laminate veneers and subgroup II, 0.3 mm thickness laminate veneers. The marginal fit was measured using stereomicroscope. The results were tabulated and statistically analyzed using two-way ANOVA test followed by Tukey’s post hoc test. Comparisons of main and simple effects were done utilizing Bonferroni correction (P ? 0.05). Results: The mean (±SD) highest marginal discrepancy was recorded in subgroup BII at 85.45±1.82 µm while the least mean marginal discrepancy was recorded in subgroup AI 71.24±2.64 µm. Conclusion: Both thicknesses (0.5 mm thickness and 0.3 mm thickness) and all tested CAD/CAM systems produced zirconia-reinforced lithium silicate laminate veneers with clinically acceptable marginal gaps; however, the closed CAD/CAM systems produced veneers with superior marginal fit than open systems at 0.3 mm thickness. The CAD/CAM system with the 5-axis milling machine produced the best marginal fit with 0.5 mm thickness. KEYWORDS Marginal fit; Zirconia-reinforced lithium silicate; Laminate veneers; CAD/CAM; Milling machines. RESUMO Objetivo: O objetivo deste estudo in vitro foi avaliar a adaptação marginal de facetas laminadas de silicato de lítio reforçado com zircônia com duas espessuras, utilizando diferentes sistemas CAD / CAM. Material e métodos: 42 facetas laminadas fresadas a partir de silicato de lítio reforçado com zircônia foram divididos em três grupos principais de acordo com a fresadora usada em: grupo X5, facetas laminadas fabricados pela fresadora inLab MCX5; grupo CM, facetas laminadas fabricados por Ceramill motion 2; e grupo XL, facetas laminadas fabricados pelo inLab MCXL. Cada grupo foi dividido em dois subgrupos, de acordo com a espessura do laminado, em: subgrupo I, facetas laminadas com 0,5 mm de espessura e subgrupo II, facetas laminadas com espessura de 0,3 mm. A adaptação marginal foi medida usando estereomicroscópio. Os resultados foram tabulados e analisados estatisticamente usando o teste ANOVA de dois fatores seguido pelo teste post hoc de Tukey. Comparações dos efeitos principais e simples foram realizadas utilizando a correção de Bonferroni (P ?0,05). Resultados: A maior discrepância marginal média (± DP) foi registrada no subgrupo BII em 85,45 ± 1,82 µm, enquanto a menor discrepância marginal média foi registrada no subgrupo AI 71,24 ± 2,64 µm. Conclusão: Ambas as espessuras (0,5 mm e 0,3 mm) e todos os sistemas CAD / CAM testados produziram facetas de laminado de silicato de lítio reforçadas com zircônia com lacunas clinicamente aceitáveis. No entanto, os sistemas CAD / CAM fechados produziam facetas com adaptação marginal superior aos sistemas abertos com 0,3 mm de espessura. O sistema CAD / CAM com a fresadora de 5 eixos produziu a melhor adaptação marginal com 0,5 mm de espessura. PALAVRAS-CHAVE Adaptação marginal; Silicato de lítio reforçado com zircônia; Facetas laminados; CAD / CAM; Fresadoras.